Pemberdayaan Masyarakat Melalui Pelatihan Pengolahan Kripik Ikan Lele dalam Meningkatkan Ekonomi Kreatif di Masa New Normal - Suharman, Suharman; Syarifah, Atika Nur (Jurnal Pengabdian kepada Masyarakat UBJ, 2021)
The KWT "Margo Mulyo" Mertosanan Wetan, Potorono Village is a community group made up of women farmers. Potorono Village has a tourist attraction in Telaga Embung, which is often packed, and there is also a lot of potential for catfish fishing. However, the community's knowledge and skills in diversifying the processing of catfish products are still limited. The catfish produced are only utilized for personal consumption, with some being sold to middlemen for a small profit. To boost the selling value of catfish, product processing innovations that may be used as mementos typical of Potorono Village are required, with the Telaga Embung tourist region as the primary marketing goal. As a result, counseling and training on the manufacturing of catfish chips as souvenirs unique to Potorono Village, Banguntapan District, Bantul Regency, Yogyakarta Special Region. This program aims to raise awareness about the nutritional value of catfish and to improve the processing abilities of the "Margo Mulyo" Farmer Women's Group. The skills required begin with the selection of raw materials and continue through product preparation, which includes washing, slicing, and seasoning preparation, to ensure that the products produced exceed nutritional and food safety criteria. Consumers appreciate the product's appearance and crispness, as well as the use of a silent machine to ensure that the final product is of high quality.